Five Hundred Sixty Nations Among Us: Understanding the Basics of Native American Sovereignty - Brimley, Stephen (Maine Policy Review, 2004)
Stephen Brimley presents a general background on the historical context of Native American tribal sovereignty on the national level, and the current political and legal environment in which tribal rights are defined. He describes how tribes have retained varying degrees of the rights they had prior to European contact, and the ways in which state power over tribes has been expanded through court action in the past several decades. Maine’s Native American groups are in a somewhat unique situation with regard to sovereignty, as defined in the Maine Indian Land Claims Settlement Act of 1980.
Keywords: Maine; Native American sovereignty; tribal sovereignty